Investigation of the Tetrakis(dimethylamino)hafnium and H2S ALD Process: Effects of Deposition Temperature and Annealing - Zsófia Baji; Zsolt Fogarassy; Attila Sulyok; Péter Petrik (Solids, 2022)
HfS2 has recently emerged as a promising 2D semiconductor, but the lack of a reliable method to produce continuous films on a large scale has hindered its spreading. The atomic layer deposition of the material with the precursor tetrakis-dimethylamino-hafnium with H2S is a relatively novel solution to this problem. This paper shows that it is a facile approach to synthesizing homogeneous and smooth HfS2 layers in a controlled and reproducible manner. The deposition is examined at different temperatures and layer thicknesses, exploring the ALD window of the deposition and the chemical, morphological and electronic properties of the films. The method yielded films with wafer-sized uniformity and controlled properties and is, thus, a promising way to prepare this important transition metal dichalcogenide material.